Techno-economic analysis of the use of waste polyethylene (pure water sachet) as a modifier for bituminuous road construction in Nigeria (2018)
JAMB UTME, the only entry route for admission into any Nigerian tertiary institution has few accredited centres having adequate facilities where registration can be carried out. This has resulted in pressure on the few accredited centres within the short timeframe allowed for registration. Thus, there is need for efficiency in the registration process to ensure that as many students as possible are registered within the short timeframe, while maximising financial turnover of registration centre operators. A JAMB UTME registration centre in Ibadan, Nigeria was studied. The requirements and procedures of the registration process were studied through personal observation and interviews during site visits, as well as questionnaires. PERT approach was used to determine the expected time for performing the registration process based on the reported values by the operators. With the aid of a stopwatch, time study was carried out on the registration process. The difference between standard and expected times was used to determine the efficiency of the centre. A cause and effect analysis was carried out to investigate the immediate and root causes of inefficiency. Information gathered include required tools and procedures involved in the registration process. The expected time was found to be 13 minutes while the standard time was discovered to be 6 minutes and 54 seconds, indicating that the efficiency level of the system was at 53%. From the cause and effect analysis, 7 immediate and 15 root causes were found to be responsible for the inefficiency observed. Finally, it was found that inefficiency exists in the process, and as such, it becomes necessary to take some remedial actions so as to improve the efficiency of the whole process.